Features of structure and dynamics in damages of fertile properties in ejaculate under the influence of toxocariasis invasion - L. L. Voroncova; S. O. Kenijz; V. A. Kovalenko (Сучасні медичні технології)
Purpose of the study. To study the features of changes of spermiologic values and degree of spermatozoa DNA fragmentation depending on the presence/absence of toxocariasis invasion.